2022
DOI: 10.1097/ico.0000000000003129
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Visual Acuity in Patients With Microbial Keratitis

Abstract: The purpose of this study was to predict visual acuity (VA) 90 days after presentation for patients with microbial keratitis (MK) from data at the initial clinical ophthalmic encounter. Methods:Patients with MK were identified in the electronic health record between August 2012 and February 2021. Random forest (RF) models were used to predict 90-day VA , 20/40 [visual impairment (VI)]. Predictors evaluated included age, sex, initial VA, and information documented in notes at presentation. Model diagnostics are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Laterality of MK was determined by ICD-10 codes when available. If ICD-10 codes were not sufficiently specific or if ICD-9 codes were used, then natural language processing of the note was applied to classify MK laterality, as has been previously described by our group . For each patient, the first date of MK diagnosis identified in the EHR was designated as the date of MK presentation.…”
Section: Methodsmentioning
confidence: 99%
“…Laterality of MK was determined by ICD-10 codes when available. If ICD-10 codes were not sufficiently specific or if ICD-9 codes were used, then natural language processing of the note was applied to classify MK laterality, as has been previously described by our group . For each patient, the first date of MK diagnosis identified in the EHR was designated as the date of MK presentation.…”
Section: Methodsmentioning
confidence: 99%
“… 59 The elderly age group has also been seen to have an increased probability of 90-day visual impairment (VA < 20/40). 62 These trends in microbial keratitis are also seen in the subgroup of bacterial keratitis where elderly patients have poor visual outcomes compared to individuals < 65 years. Specifically, Ly et al reported that their poor outcome subgroup had an average age of 67 years compared to 50 years.…”
Section: Characteristics and Treatment Of Infectious Keratitis In The...mentioning
confidence: 97%